The Government of Canada's Search for Environmental Legitimacy: 1971-2008 - Macdonald, Douglas (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractAlthough the term "greenwash" has now entered the language, there has beenlittle academic analysis of environmental legitimacy as a factor in environmentalpolitics. This article examines claims to environmental legitimacy made by theGovernment of Canada with respect to seven policy initiatives. The most commonclaims have been: (1) action exceeds that of previous governments; (2) Canada isdoing more than other countries; (3) the policy will aid economy as well asenvironment (sustainable development); and, (4) the transparent policy process isitself legitimate. Exaggeration and downplaying related action by the provinces areother common themes.